2012
DOI: 10.1007/s10750-011-0995-7
|View full text |Cite
|
Sign up to set email alerts
|

Iron addition as a shallow lake restoration measure: impacts on charophyte growth

Abstract: Eutrophication has caused a decline of charophyte species in many shallow lakes in Europe. Even though external inputs of phosphorus are declining, internal loading of P from the sediment seems to delay the recovery of these systems. Iron is a useful chemical binding agent to combat internal phosphorus loading. However, the effects of iron addition on charophytes are not yet known. In this study we experimentally tested the potential toxicity of iron(III)chloride (FeCl 3 ) on two different charophytes, Chara v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 39 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…St. John, Potamogeton pectinatus L. 1753 (Immers et al 2014), P. acutifolius Link 1818, Stratiotes aloides L. 1753 (Van der Welle et al 2006, 2007b, Myriophyllum aquaticum (Vell.) Verdc (Kamal 2004) and the charophyte species Chara virgata Kützing 1834 and C. globularis Thuiller 1799 (Immers et al 2013). Experiments with macrophytes growing in industrial metal-rich areas (8.6 mg Fe L -1 in surface water and 0.75 mg Fe g -1 sediment of which 0.21 exchangeable Fe) also showed that aquatic macrophytes were able to grow well without showing any external abnormalities (Nayek et al 2010).…”
Section: Primary Producersmentioning
confidence: 98%
“…St. John, Potamogeton pectinatus L. 1753 (Immers et al 2014), P. acutifolius Link 1818, Stratiotes aloides L. 1753 (Van der Welle et al 2006, 2007b, Myriophyllum aquaticum (Vell.) Verdc (Kamal 2004) and the charophyte species Chara virgata Kützing 1834 and C. globularis Thuiller 1799 (Immers et al 2013). Experiments with macrophytes growing in industrial metal-rich areas (8.6 mg Fe L -1 in surface water and 0.75 mg Fe g -1 sediment of which 0.21 exchangeable Fe) also showed that aquatic macrophytes were able to grow well without showing any external abnormalities (Nayek et al 2010).…”
Section: Primary Producersmentioning
confidence: 98%
“…Aluminum and iron salts were able to inhibit the release of phosphorus (P) from sediment by combining with soluble reactive phosphorus (SRP) to form insoluble precipitants (Liu et al 2009). However, aluminum can be toxic to aquatic organisms (Pessot et al 2014), and the effect of iron salt is sensitive to redox and pH conditions (Burley et al 2001;Immers et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In the first stage of the experiment, limited penetration of radiation was caused by heavy water turbidity and iridescence. Once these optical conditions ceased and water clarity improved, flock coagulants settled on the charophyte and formed a colloid film limiting/reflecting light access (Immers et al 2013). In such a situation the charophyte grew to reach the water surface, which was a typical defense reaction to shading (Blindow and Schütte 2007).…”
Section: Discussionmentioning
confidence: 99%